Employee-friendly labour time: a key element to a sustainable pattern of production and consumption. (30th March 2010) - Groezinger, Gerd; Matiaske, Wenzel; Tobsch, Verena
Whereas the preferences of consumers are a cornerstone of market economies, the preferences of employees, e.g., regarding the preferred amount of paid labour, usually are not. However, we have strong evidence that differences between aspired and actually worked weekly hours have a serious negative impact on life, job and health satisfaction. This paper investigates the gap between employees' preferences and the realities by means of the German Socio-Economic Panel (GSOEP) 2004 data. The central question analysed is, How many hours would one like to work, taking into account that earnings would change accordingly? A majority of German employees desired a reduction and only a small minority preferred an enlargement. By combining both effects, more than 2.4 million additional employees could have been statistically brought into work again, satisfaction would have been improved and consumerism somewhat mellowed. And, since mainly persons with children wanted to reduce their working hours, family life would have gained significantly.